A tabu search approach to the cargo prioritisation and terminal allocation problem. (8th April 2020) - Tong, Jingjing; Nachtmann, Heather
To mitigate inland waterway disruption impacts, we develop a tabu search (TS) approach to solve the cargo prioritisation and terminal allocation problem (CPTAP) to minimise the total value loss of disrupted barge cargoes by offloading the cargoes to the land transportation modes. CPTAP is formulated as a nonlinear binary integer program, and problems of realistic size can be efficiently and effectively solved with an efficient heuristic approach. Given different neighbourhood structures, multiple TS variants are attempted and compared. Solving CPTAP with our TS heuristic leads to the lowest cargo value loss and the shortest response time for the disrupted barges compared to a genetic algorithm approach and a na